2017
DOI: 10.5603/cj.a2017.0051
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic evaluation of right ventricular systolic function: The traditional and innovative approach

Abstract: Estimation of right ventricular (RV) performance still remains technically challenging due to its anatomical and functional distinctiveness. The current guidelines for the echocardiographic quantification of RV function recommend using multiple indices to describe the RV in a thorough and comprehensive manner, such as RV index of myocardial performance, tricuspid annular plane systolic excursion, fractional area change, Doppler tissue imaging-derived tricuspid lateral annular systolic velocity (S'-wave), three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
73
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 56 publications
0
73
0
2
Order By: Relevance
“…Of interest, the SD for the FAC of the left ventricle became progressively smaller between 20 and 40 weeks of gestation, while it changed minimally for the right ventricle over the same time period. This may reflect more efficient function of the left ventricle as a result of the interaction and maturation of its longitudinal, circumferential and oblique muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, the SD for the FAC of the left ventricle became progressively smaller between 20 and 40 weeks of gestation, while it changed minimally for the right ventricle over the same time period. This may reflect more efficient function of the left ventricle as a result of the interaction and maturation of its longitudinal, circumferential and oblique muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…In adult and pediatric patients, the right ventricle is triangular in shape in the coronal plane and crescent‐shaped in the transverse plane, thus not allowing the examiner to use Simpson's rule to compute the ejection fraction. A surrogate for evaluating right ventricular systolic function is measurement of the FAC from the four‐chamber view; it has been shown to identify cardiac dysfunction in neonates, pediatric and adult patients, and is correlated with right ventricular ejection fraction measured with magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no accurate index to assess RV function. RV Tei index, tricuspid annular plane systolic excursion (TAPSE) and RV area change fraction (RVFAC) are currently the most commonly used methods for evaluating RV contractile function [31][32][33][34]. This meta-analysis found that PADN did not signi cantly change the Tei index of PH, which might be due to too little data Moreover, TAPSE and RVFAC are incomplete, so metaanalysis cannot be performed.…”
Section: Discussionmentioning
confidence: 94%
“…The two-dimensional echocardiography has some important limitations in the assessment of RV [8]. This cardiac chamber has a unique crescent shape and no geometrical assumption can be made.…”
Section: Discussionmentioning
confidence: 99%